EXPLORING PERCEPTIONS AND EXPERIENCES OF GREEN CONCRETE AND ITS VIABILITY AS A SUSTAINABLE ALTERNATIVE: A QUALITATIVE STUDY - Alhussein Marzuk; M. Ikhsan Setiawan; Ronny Durrotun; Rizal Bahaswan; Adi Prawito (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
This study aims to investigate green concrete as a sustainable alternative to traditional concrete by examining its properties, performance, and durability. The research will analyze data from previous qualitative studies and case studies using thematic analysis. Then a comparative analysis of green concrete and traditional concrete will be used for their properties, performance, and durability. The findings will contribute to the understanding of green concrete and its potential applications in the construction industry. Additionally, the study will evaluate the economic and environmental implications of using green concrete and provide recommendations for its adoption. The research methodology includes a comprehensive literature review, data collection, analysis, and discussion of the results. as conclusion Green concrete offers significant benefits for the construction industry. It reduces waste and carbon impact by using recycled materials, improves mechanical qualities, durability, and environmental performance, and is more cost-effective and durable. However, the use of recycled concrete aggregate has a slightly reduced impact on economic and environmental benefits in high-performance concretes